Computerized dynamic occlusal analysis and its correlation with static characters in post-orthodontic patients using the T-Scan system and the ABO objective grading system - Menglin Wang; Le Liu; Xihua Ma; Xiang Jin; Zhenbao Zhang; Xiangmin Jia; Jiadong Fan; Haoning Tang; Yanfeng Li (BMC, 2023)
Abstract Objectives This study was conducted to detect the overall performance of both static and dynamic occlusion in post-orthodontic patients using quantified methods, and to ascertain the correlation between the two states of occlusion. Materials and methods A total of 112 consecutive patients evaluated by ABO-OGS were included in this study. Based on the pre-treatment Angle's classification of the malocclusion, samples were divided into four groups. After removing orthodontic appliances, each patients underwent the American Board of Orthodontic objective grading system (ABO-OGS) and T-Scan evaluations. All the scores were compared within these groups. Statistical evaluation included reliability tests, multivariate ANOVA, and correlation analyses (p < 0.05 was considered significant). Results The mean ABO-OGS score was satisfactory and did not differ by Angle classifications. The indices making substantial contributions to ABO-OGS were occlusal contacts, occlusal relationships, overjet, and alignment. Disocclusion time in post-orthodontic patients was longer than normal. Occlusion time, disocclusion time, and force distribution during dynamic motions were considerably influenced by static ABO-OGS measurements, especially occlusal contacts, buccolingual inclination, and alignment. Conclusion Post-orthodontic cases that passed the static evaluation of clinicians and ABO-OGS may nevertheless be left with dental casts interference in dynamic motions. Both static and dynamic occlusion should be extensively evaluated before ending orthodontic treatment. Further research is needed on dynamic occlusal guidelines and standards.